UPAYA ENVIRONMENTAL MOVEMENT DALAM MENGURANGI KETERGANTUNGAN PERANCIS TERHADAP PENGGUNAAN ENERGI NUKLIR - Nanda Micolla; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study discusses "Environmental Movement Efforts in Reducing French Dependence on Nuclear Energy Use". Nuclear energy in France is used for commercial power plants. France's excessive dependence on the use of nuclear energy causes various environmental losses and problems, such as nuclear accidents and dangerous toxic waste. As a result of the problem came the environmental movement that requires that France reduce its dependence on nuclear energy and replace it with renewable energy.The method used in this research is qualitative explanative. This research uses secondary data by using library research. This study uses Pluralism Perspective by Paul R, Viotti and Mark V.Kauppi, Level of Group Behavioral Analysis, and Theory of Social Movement by Robert Misel.The result of this research is the Environmental Movement in France made efforts by conducting campaigns and establishing an international network to rally public opinion so that the French government reduce its dependence on the use of nuclear energy. This effort is quite successful with the declining percentage of French electricity production from nuclear energy and the government's commitment to this problem with the draft law on the decline in electricity production from nuclear power.Keywords : Nuclear Energy, Pluralism, Social Movement, International Network, Environmental Movement